Analisis Current Ratio, Debt To Equity Ratio, Total Assets Turn Over dan Net Profit Margin dalam Menilai Kinerja Keuangan Perusahaan Sektor Aneka Industri pada Bursa Efek Indonesia 2016-2019 - Rosalinda Tania; Benny Rojeston Marnaek Nainggolan (Politeknik Ganesha Medan, 2021)
This study aims to analyze and know the influence of Current Ratio, Debt To Equity Ratio, Total Assets Turn Over and Net Profit Margin in assessing the Financial Performance of Multi-Industry Sector Companies in the period 2016-2019. Independent variables used are Current Ratio, Debt To Equity Ratio, Total Assets Turn Over and Net Profit Margin while dependent variable in this study is Financial Performance represented by Return On Asset. The method used is quantitative method, The type of research is correlation between connecting independent and dependent variable. Research described causal relationship. The sampling technique used is purposive sampling. Sample is defined as part of the population with certain criteria and amount. Samples used in the study of 13 companies. The tests used are classic assumption tests, multiple linear analysis research models, and the coefficients of determination are simultaneous and partial tests. The results showed that partial current ratio and debt to equity ratio have no effect on financial performance while Total Assets Turn Over and Net Profit Margin affect financial performance. Adjusted R Square test results explain 97.4% of dependent variables can be explained by independent variables while the remaining 2.6% is not explained. The conclusion from the results of this test that two variables namely Current ratio and Debt To Equity Ratio which does not affect Financial Performance.